Farmers’ Perception for Bio-Slurry Fertilizer in Central Java - Malinda Aptika Rachmah; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2021)
Bio-slurry is an organic fertilizer derived from the residual waste of biogas processing. This study aims to: 1) find out farmers’ perception of bio-slurry fertilizer, 2) determine the socio-economic characteristics of farmers who confirm to adopt bio-slurry fertilizer in the future. The study was conducted from January to February 2020 in Central Java. Determination of location was purposive with the consideration that farmers in Magelang and Demak Regency, who had utilized biogas waste and commercialized it. Primary data was obtained from 80 by accidental sampling. Data analysis used the attributes of innovation: relative advantage, compatibility, complexity, trialability, and observability to measure farmers’ perceptions and cross tabs to determine the distribution of confirmation to adopting/stop adopting bio-slurry fertilizers. The results showed that farmers’ perceptions of the relative advantage and trialability of bio-slurry fertilizer were moderately satisfied, completely satisfied perceptions of compatibility, very satisfied with the complexity, and observability of using bio-slurry fertilizers. Respondents who confirmed to adopt bio-slurry fertilizer had characteristics: 1) income of around IDR 2,100,000-3,000,000/month and Rp. 5,000,000/month; 2) have a high school level education; 3) have land ownership area 0.5 ha; 4) have an age between 41-50 years, and 5) have 3-4 family members. Farmer satisfaction level indicates the good opportunity to survive in the market by taking into account quality.